Application of FT-IR Spectroscopy for Fingerprinting of Zymomonas mobilis Respiratory Mutants. Issue 5 (11th July 2012) - Grube Grube, M. M.; Rutkis Rutkis, R. R.; Gavare Gavare, M. M.; Lasa Lasa, Z. Z.; Strazdina Strazdina, I. I.; Galinina Galinina, N. N.; Kalnenieks Kalnenieks, U. U.
Abstract : Z. mobilis ATCC 29191 and its respiratory knockout mutants, kat-, ndh-, cytB-, and cydB-, were grown under anaerobic and aerobic conditions. FT-IR spectroscopy was used to study the variations of the cell macromolecular composition. Quantitative analysis showed that the concentration ratios—nucleic acids to lipids, for Z. mobilis parent strain, kat-, ndh-, cytB-, and cydB- strains, clearly distinguished Z. mobilis parent strain from its mutant derivatives and corresponded fairly well to the expected degree of biochemical similarity between the strains. Two different FT-IR-spectra hierarchical cluster analysis (HCA) methods were created to differentiate Z. mobilis parent strain and respiratory knockout mutant strains. HCA based on discriminative spectra ranges of carbohydrates, nucleic acids, and lipids allowed to evaluate the influence of growth environment (aeration, growth phase) on the macromolecular composition of cells and differentiate the strains. HCA based on IR spectra of inoculums, in a diagnostic region including the characteristic nucleic acid vibration modes, clearly discriminated the strains under study. Thus it was shown that FT-IR spectroscopy can distinguish various alterations of Z. mobilis respiratory metabolism by HCA of biomass spectra.